Assessment of diagnostic reasoning in acute vertigo using vignette-based tools: A cross-sectional comparison between general practitioners and final-year medical students - Charles Maquet; Maxime Wojtecki; Alexandre Tendron; Sophie Deneuve; Honorine Claudot; Frederic Crampon; Julien Burel (PLoS ONE, 2026)
Background Acute vertigo is a frequent reason for consultation in primary care and poses diagnostic challenges for general practitioners. Although vestibular disorders are addressed during undergraduate medical training, knowledge retention over time is uncertain, while clinical experience accumulates with practice and may contribute to refining diagnostic reasoning. However, how diagnostic reasoning in acute vertigo evolves between the end of initial medical training and routine general practice remains poorly understood. Validated vignette-based tools, such as Script Concordance Tests and Key Feature Problems, enable standardized assessment of diagnostic reasoning. This study compares diagnostic reasoning in acute vertigo between final-year medical students and practicing general practitioners. Methods and findings This cross-sectional observational study was conducted between January and March 2024 in a French region. Participants included general practitioners (GPs) in active practice and final-year medical students. All participants completed a self-administered questionnaire based on standardized clinical vignettes representing common presentations of acute vertigo. Diagnostic reasoning was assessed using two validated educational tools: Script Concordance Tests and Key Feature Problems. Scoring keys were established through consensus among 20 expert otolaryngologists. Diagnostic reasoning was expressed as the percentage of correct responses. Associations between diagnostic reasoning and participant characteristics, including clinical experience, consultation volume, vertigo-specific continuing medical education, and self-reported confidence in vertigo management, were analyzed using univariate and multivariate models. A total of 265 participants were included, comprising 173 general practitioners and 92 final-year medical students. Medical students achieved significantly higher diagnostic reasoning scores than GPs (61.0% vs. 54.0%, p < 0.001). Among GPs, higher scores were associated with lower daily consultation volumes (<30 patients/day), prior vertigo-specific continuing medical education, and greater self-reported confidence in the management of acute vertigo. In multivariate analysis, vertigo-specific continuing medical education (β = 0.77; 95% CI, 0.03–1.51; p = 0.041) and self-reported confidence (β = 1.45; 95% CI, 0.54–2.36; p = 0.002) remained independently associated with better diagnostic reasoning. Conclusion In this study, final-year medical students outperformed practicing general practitioners on vignette-based assessments of diagnostic reasoning in acute vertigo. The observed difference may be related to differences in recent theoretical exposure and training background. Targeted continuing medical education could be further evaluated as a strategy to support diagnostic reasoning and confidence among general practitioners in primary care.